Integrated Flood Risk and Embankment Stability Modeling in the Comoro River, Timor-Leste using HEC-RAS and GIS - Kris Minaryo; Hanie Teki Tjendani; Esti Wulandari; Rahmad Junaidi; Andiyan Andiyan; Shreeniwas Omanwar (CV FOUNDAE, 2025)
Dili, the capital city of Timor-Leste, is increasingly vulnerable to flooding due to its geomorphological characteristics and rapid urban expansion. The Comoro River, the largest of several rivers traversing the city, has experienced multiple significant flood events in recent years most notably in March 2020, April 2021, and February 2022 resulting in severe damage to infrastructure and disruption to local communities. Urban development has led to watershed degradation, sediment accumulation, reduced channel capacity, and embankment overtopping, exacerbating flood risks in densely populated areas. This study aims to assess flood risk and evaluate embankment resilience using an integrated modeling approach. Design flood discharge was estimated using the Log Pearson Type III distribution and the Nakayasu synthetic unit hydrograph, with validation through Chi-Square and Kolmogorov-Smirnov goodness-of-fit tests. Hydraulic simulations were conducted using HEC-RAS 6.1.0 programme, while flood inundation mapping was performed with ArcGIS 10.3 to identify critical flood-prone zones and guide mitigation strategies. Results indicate a peak discharge of 192.141 m³/s for a 25-year return period flood. Mitigation measures proposed include embankment construction and river normalization at vulnerable cross-sections. HEC-RAS simulations demonstrate that these interventions significantly reduce flood inundation. The embankment slope stability factor was calculated at 7.55, indicating a high level of structural safety. The estimated cost for implementing these flood control measures is USD 571,366.87. This study provides a replicable framework for flood hazard modeling and infrastructure planning in urban river systems, contributing to climate-resilient development and evidence-based decision-making in Southeast Asian contexts.